Collaborative Governance : Private Roles for Public Goals in Turbulent Times - Donahue, John D.; Zeckhauser, Richard J. (Princeton University Press, 2011)
All too often government lacks the skill, the will, and the wallet to meet its missions. Schools fall short of the mark while roads and bridges fall into disrepair. Health care costs too much and delivers too little. Budgets bleed red ink as the cost of services citizens want outstrips the taxes they are willing to pay. Collaborative Governance is the first book to offer solutions by demonstrating how government at every level can engage the private sector to overcome seemingly insurmountable problems and achieve public goals more effectively. John Donahue and Richard Zeckhauser show how the public sector can harness private expertise to bolster productivity, capture information, and augment resources. The authors explain how private engagement in public missions--rightly structured and skillfully managed--is not so much an alternative to government as the way smart government ought to operate. The key is to carefully and strategically grant discretion to private entities, whether for-profit or nonprofit, in ways that simultaneously motivate and empower them to create public value. Drawing on a host of real-world examples-including charter schools, job training, and the resurrection of New York's Central Park--they show how, when, and why collaboration works, and also under what circumstances it doesn't. Collaborative Governance reveals how the collaborative approach can be used to tap the resourcefulness and entrepreneurship of the private sector, and improvise fresh, flexible solutions to today's most pressing public challenges.